Usefulness of Ki-67 in the histological evaluation of neoplastic lesions of central nervous system - Shrestha, P; Shrestha, I; Kurisu, K (Journal of Institute of Medicine Nepal, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Ki-67 is an intranuclear protein, which is present in the proliferating cells. Since it is expressed in only dividing cells, it is an excellent indicator of tissue proliferation in neoplastic lesions. Immunohistochemistry is used to detect Ki67 in tumor tissues. Here, we present few cases where Ki-67 evaluation was very helpful in making final diagnosis. Cases- Case no. 1 was a case of intracranial mass lesion whose histological finding was confusing, pituitary tumor or astrocytoma. Ki-67 evaluation along with other factors helped in making diagnosis of pituitary adenoma. Case no. 2 was another case of intracranial mass. Ki-67 evaluation ruled out possibility of benign lesion, melanocytoma, though histologically the lesion was not clearly malignant melanoma. Case no. 3 was a case of peripheral spinal nerve tumor, a schwannoma. Its Ki-67 evaluation confirmed that it was of conventional type not cellular. Ki-67 is a marker of tissue proliferation and higher the Ki-67 expression, higher is the tumor grade and poorer is the prognosis. It also helps in concluding the diagnosis when the histological picture alone is not conclusive. Thus complete histological evaluation, including Ki-67, is necessary before making final diagnosis. Key words: immunohistochemistry, Ki-67, MIB-1, CNS tumors Journal of Institute of Medicine, April, 2008; 30:1 68-71 The full text of this paper is available from the Journal of Institute of Medicine website